The use of computer diagnostic apps to assist computer troubleshooting / Mohd Saharudin Abuludin, Norazuwa Salehudin and Beny Yusmar - Abuludin, Mohd Saharudin; Salehudin, Norazuwa; Yusmar, Beny (Faculty of Computer and Mathematical Sciences, 2023)
Electrical and electronic equipment has become significant in human life. One of them is the use of computers which are proven to be able to simplify and solve the problems faced by humans in their daily activities. These electrical and electronic equipment may cause problems while being used. The problems encountered may be simple and can be solved in a short time and independently by the user. Self-problem-solving methods have been widely applied to help people try to solve the problems they face based on the instructions given either printed or digital. This innovation digitizes the identification and repair flow chart against damage that occurs during computer use. This innovation has produced a simple application called the Computer Diagnostic App to help computer users try to solve the problems encountered while using the computer. The design of this application is based on a complete flow chart for the identification of computer problems published widely on the web and has become a reference worldwide based on the findings of the Google search engine. A survey was also conducted among lecturers of Malaysia Community College to get feedback and find out the effectiveness of using this application to solve problems that arise when using the computer.